Genome-Edited, TH-expressing Neuroblastoma Cells as a Disease Model for Dopamine-Related Disorders: A Proof-of-Concept Study on DJ-1-deficient Parkinsonism - Prasuhn, Jannik; Mårtensson, Christoph U.; Krajka, Victor; Klein, Christine; Rakovic, Aleksandar (Frontiers in Cellular Neuroscience, 2018)
Impairment of the dopaminergic (DA) system is a common cause of several movement disorders including Parkinson’s disease (PD), however, little is known about the underlying disease mechanisms. The recent development of stem-cell-based protocols for the generation of DA neurons partially solved this issue, however, this technology is costly and time-consuming. Commonly used cell lines, i.e. neuroblastoma (SHSY5Y) and PC12 cells are still widely used to investigate PD and significantly contributed to our understanding of mechanisms involved in development of the disease. However, they either do not express DA at all or require additional, only partially efficient differentiations in order to produce DA. Here we generated and characterized transgenic SH-SY5Y cells, ectopically expressing tyrosine hydroxylase (SHTH+), that can be used as a homogenous, DA-producing model to study alterations in DA metabolism and oxidative stress. We demonstrated that SHTH+ produce high levels of DA, 3,4-dihydroxyphenylacetic acid (DOPAC), and homovanillic acid (HVA) making this model suitable to investigate not only alterations in DA synthesis but also its turnover. We also provide evidence for the presence of other enzymes involved in DA synthesis and its turnover in these cells. Finally, we showed that these cells can easily be genetically modified using CRISPR/Cas9 technology in order to study genetically defined forms of movement disorders using DJ1-linked PD as a model.